2020
DOI: 10.1007/s00432-020-03127-8
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MALAT1 facilitates the tumorigenesis, invasion and glycolysis of multiple myeloma via miR-1271-5p/SOX13 axis

Abstract: Background Long non-coding RNAs (lncRNAs) play crucial roles in the regulation and treatment of multiple myeloma (MM). The objective of this research was to study the functional mechanism of metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in MM. Methods MALAT1, microRNA-1271-5p (miR-1271-5p), and SRY-Box 13 (SOX13) levels were examined by quantitative real-time polymerase chain reaction (qRT-PCR). Cell viability, apoptosis, and invasion were respectively assayed using 3-(4, 5-dimethylthiazol-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 41 publications
1
48
0
2
Order By: Relevance
“…15,16 More importantly, a previous study indicated that MALAT1 could target miR-1271-5p to participate in the tumorigenesis of multiple myeloma. 17 However, the role and underlying mechanism of miR-1271-5p in DDP resistance of OC cells is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 More importantly, a previous study indicated that MALAT1 could target miR-1271-5p to participate in the tumorigenesis of multiple myeloma. 17 However, the role and underlying mechanism of miR-1271-5p in DDP resistance of OC cells is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…At second, we probed into the mechanism of magnolol. It has been discovered that miR miR-342-3p and miR-124-3p are involved in suppression of MM [41][42][43][44][45][46]. The same results were also performed in detection of Cyclin D1, MMP-7 and MMP-9 protein expression levels through western blot.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, LncRNA HOTAIRM1, which has dual properties as it interacts with both onco-suppressor and oncogenic miRs. HOTAIRM1 is located on human HOXA gene cluster and suggested to be involved in myeloid cell development [ 176 ]. A newly published article has shown the anti-tumor activity of lncRNA HOTAIRM1 by up-regulation of ARHGAP24 through miR-106a-5p inhibition [ 177 ].…”
Section: Microrna Ncrna and Zeb: Role In Emt And Cancer Metastasmentioning
confidence: 99%